Assessment of invasion of Ageratina adenophora in the plantation forest of Nepal - Malla, R.; Aryal, R. R.; Ranabhat, S. (Banko Janakari, 2021)
Large-scale plantations of pine species were done in the bare hills of the Middle Mountain region of Nepal during the early 1980s. There is a growing concern on the sustainability of the planted pine forests in the country due to the presence of invasive alien plant species (IAPS). Invasive alien plant species are considered as one of the drivers of forest degradation and deforestation. Ageratina adenophora is one of the problematic IAPS found in the planted pine forests throughout the country. In this study, we employed different treatments to control the invasion of A. adenophora in the planted pine (Pinus patula) forest. The research design included four different treatments, viz., (i) control, (ii) stem felling, (iii) floor clearance, and (iv) stem felling cum floor clearance in one block (Block I), which was replicated in another block (Block II). The data were collected using circular sample plots with 2m radius. The ANOVA and TukeyHSD Tests were applied during the analysis process so as to determine the effects of treatments on invasion of A. adenophora. The "floor clearance treatment" was found to be significantly effective to reduce the presence of A. adenophora in the planted pine forest. On the contrary, the "opening of forest cover treatment" was found to be conducive to this invasive species to invade the area. The "stem felling cum floor clearance treatment" could be an effective strategy to control invasion of A. adenophora in planted forest, but as it demands a high cost, it is likely to be appropriate for small forest areas where promotion of regeneration is of high priority.